2020
DOI: 10.1002/pa.2220
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and inequality in Odisha, India

Abstract: Odisha has gone on from being the most underdeveloped Indian state to be the state that has recorded the highest decline in poverty among the states. We undertake decomposition analyses to assess the redistributive changes in poverty and inequality over the period 1993–1994 and 2011–2012 across regions and social groups, examining the NSSO Consumer Expenditure Survey data. We find that while Odisha has succeeded in substantially reducing both rural and urban poverty incidence, this change has not met desirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…The growth effect shifted up in the reform period, which helped to reduce poverty, and the inequality effect fell during this period. Using the Bhanumurthy and Mitra (2004) methodology, Panda and Padhi (2020) analysed poverty decomposition for Odisha, and found that growth effect has higher share than inequality effect and population shift effect on poverty reduction. In the present article, the analysis of the modified Kakwani poverty decomposition methodology has been directly derived from Bhanumurthy and Mitra (2004).…”
Section: Methodsmentioning
confidence: 99%
“…The growth effect shifted up in the reform period, which helped to reduce poverty, and the inequality effect fell during this period. Using the Bhanumurthy and Mitra (2004) methodology, Panda and Padhi (2020) analysed poverty decomposition for Odisha, and found that growth effect has higher share than inequality effect and population shift effect on poverty reduction. In the present article, the analysis of the modified Kakwani poverty decomposition methodology has been directly derived from Bhanumurthy and Mitra (2004).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, Odisha has hogged limelight for its considerably impressive records on economic growth (e.g., see Sahu & Panda, 2018) and poverty alleviation and inequality reduction (e.g., see Panda & Padhi, 2020) vis‐à‐vis other major Indian states. In fact, an empirically rigorous study by Sahu and Panda (2018) found that the period contemporaneous to the Naveen Patnaik regime has seen higher growth performance of Odisha compared to its own history, the national economy, and 15 other major states.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Mr. Naveen Patnaik, the chairman of Biju Janata Dal, a regional political party, has been the Chief Minister of the state since March 2000 and has been only one of the three Chief Ministers in India's history to have won five consecutive terms in office (the other two being Jyoti Basu in West Bengal and Pawan Kumar Chamling in Sikkim). The state's performance on poverty eradication has been spectacular: it has gone on from being the most underdeveloped state (see, e.g., Government of India, 2013) to be the state that has recorded the highest decline in poverty among the states (Panda & Padhi, 2020) and most impressive economic growth among the major states (Sahu & Panda, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although caste inequality has reduced in some states in India, particularly the south (Chakrabarti, 2021 ), caste discrimination is still rife in many contexts, including in health and nutrition services (John, 2018 ; Mosse, 2018 ; Deshpande, 2019 ), and in Odisha, those belonging to ST and SC groups experience worse outcomes compared to other caste categories as shown by recent National Family Health Survey five (NFHS V) data (IIPS, 2021 ). The literacy rate of ST and SC groups in Odisha is 52.2% and 69% respectively, well below that of the total for the state 72.9% (NFHS V) and poverty rates for ST and SC populations remain extremely high, with ST groups at 63% and SC groups at 41% compared with the state level 33% (Panda & Padhi, 2021 ). The districts that were part of this study, known as the ‘KBK + ’ districts (pertaining to the older boundaries of Kalahandi, Koraput and Balangir, now divided amongst several other districts), are known to be amongst the most deprived in Odisha and in India.…”
Section: Introductionmentioning
confidence: 99%